Fracture toughness properties and characteristics of Friction stir welded high strength aluminium alloy by post weld heat treatment (PWHT). (2021) - Sivaraj, P.; Seeman, M.; Seetharaman, R.; Balasubramanian, V.
Abstract: This paper presents the PWHTed effects on fracture toughness properties on stir-welded AA7075 aluminum alloy joints. 12-mm thick rolled AA7075-T651 plates were joined. The joints were given post-weld heat treated by STA and AA. Compact tension (CT) specimens were prepared to evaluate the plane strain fracture toughness of the welded joints. The fracture toughness properties were evaluated under uniaxial tensile loading conditions (stress ratio = 0.1, Frequency = 10 Hz) at room temperature using a servo-hydraulic controlled machine. The welded joints microstructures were examined by low magnification microscopy (OM) and high magnification microscopy (TEM) techniques. It is found that the joint treated with the solutionizing followed by artificial aging cycle exhibited superior fracture toughness properties compared to as-welded joint and artificially aged joints.